Analyzing neural response to visual stimuli: Firing rates, frequency band dynamics, and synchrony in near and far flanker conditions - Kunwar, Manjeet; Bhusal, Nabin; Dhital, Niraj (Himalayan Physics, 2025)
The present work investigates how spatial configurations of distractor stimuli influence neural processing during visual perception, specifically contrasting Near and Far flanker conditions. Electroencephalography (EEG) recordings of 50 people were obtained from an online open-access database called OpenNeuro and evenly assigned to each condition. A multimodal analytical approach was employed, incorporating spectrogram analysis, wavelet transformation, time-frequency decomposition, and cross-correlation to comprehensively characterize neural activity. Inferred neural firing rates were examined to assess differences in cognitive engagement. Results indicate that the Near flanker condition elicited increased delta and theta band power in frontal regions and higher estimated firing rates, suggesting elevated cognitive load and attentional demands. In contrast, the Far condition exhibited greater alpha and beta activity, consistent with more efficient neural processing. Despite these trends, statistical analysis revealed no significant difference in firing rates between the two conditions (p = 0.735). These findings highlight the impact of spatial context on attentional modulation and underscore the utility of EEG-based measures for probing the neural mechanisms underlying visual cognition.